Coloração do tegumento relacionada à permeabilidade e dormência física de sementes de Albizia lebbeck (L.) Benth - Brito, Carlayle Alves de (2016)
In response to drought stress, it is common on Fabacea family s species to develop physical dormancy imposed by the impermeability of the tegument. In the present study, the aim was to correlate the seed s coloration resulting from the different stages of maturity with the permeability degree of the teguments, the water and the Albizia lebbeck seed s germination. Besides that, this project aimed to determine the harvesting stage of fruits that precedes the installment of the dormancy on the seeds. The soaking and germination of freshly harvested seed s samples colored pattern extremely green (EG), green (G), light brown (LB), greenish brown (GB) and dark brown (DB) , stored for 60 days, was assessed. After 53 days of soaking there were elaborated and analyzed curves of water intake with individual weighting and sequential of 10 seeds for each coloration pattern. The germination experiments were conducted on a BOD greenhouse incubator and organized in 5 repetitions of 20 seeds for each coloration. The seeds were laid over blotting paper leafs on seed boxes conditioned to the temperature of 25º±1ºC with a 12 hour photoperiod. Daily scores of the germinated seeds were kept until the 32nd day. After that period the scores were kept every 72 hours, until 77 days were completed. The germination criteria adopted was the emission of the primary root with the geotropic curvature. The experiments results show that on the transmition of the EG pattern seeds to the DB pattern seeds there was a high reduction on the water content, from 57,3 % to 14,09%, respectively. The EG and G lots showed high permeability to water and in the process to the brown coloration this permeability was highly reduced with 70% of the DB seeds not soaking. For freshly picked EG and G the germination was high, 95% and 94%, respectively, reflecting the tegument high permeability. On the intermediate and final phases of patterns LB, GB and DB maturation, they showed a fall on the percentages of germination, being this respectively, 72%, 76% and 32%, and also a high mortality of seeds, 23%, 21% and 37%. When stored for 60 days, the EG seed s germination quality was not affected by the dehydration, keeping a high percentage (99%). G, LG and GB showed a fall on the germination capacity when stored, 68%, 45% and 58%, respectively, and the germination response of DB seeds was low on both tests, 32% and 33%. Albizia lebbeck seeds with a high water content (36,4% and 57,3%) and green coloration, don t show any restrictions to soaking and those harvested on the DB stage, with reduced water content (14,09%) have a high level of impermeability. EG seeds extracted from green fruits don t have physical dormancy and when stored for up to 60 days the dehydration doesn t impose dormancy. The seeds become dormant with the dehydration advance until levels near 11% of humidity are reached. The seeds extracted from green and slightly yellow fruits, have a higher germination capacity than those extracted from yellow fruits.